On additivity of derivations - Sandhu, G.S.; Kumar, D. (Carpathian Mathematical Publications, 2019)
Let $R$ be a ring and $M$ be an $R$-bimodule. A mapping $d:R→ M$ (not necessarily additive) is called multiplicative derivation of $R$ if $d(xy)=d(x)y+xd(y)$ for all $x,y\in R.$ In this paper, we intend to establish the additivity of $d$ under some suitable restrictions. Moreover, we introduce multiplicative semi-derivations of rings and discuss their additivity.